The Impact of Climate Change on Nature in Life As We Knew It by Susan Beth Pfeffer - Rizal, Salsabila Fajrina; Najma, Eva; Pratiwi, Dyani Prades (LingoLitera, 2026)
This thesis examines what are the impacts of climate change on nature as portrayed in the young adult novel Life As We Knew It by Susan Beth Pfeffer. The focus of this research is to find out the impact of sudden climate change caused by the “Moon Crush” incident. Ecocriticism is applied as the primary theoretical framework, particularly Greg Garrard’s ecocriticism concept of “Apocalypse”. A qualitative method is applied, using the novel as the main data source and other relevant sources as the secondary data. As a result of the research, the writers found that Life As We Knew It effectively illustrates the potential real-life outcomes of a “Moon Crush,” showing a strong connection to scientific data. This research concludes that the moon has a significant influence on the Earth; if the moon were to leave its orbit, the Earth would experience disasters such as massive tsunamis and extreme climate changes. The impacts of climate change depicted in this novel include drastic temperature drops, crop failures, and resource scarcity. The writers emphasize that humans and nature are mutually dependent. Humans rely on nature for their survival, while nature is affected by human activities, which can either harm or help maintain the balance of the ecosystem.